FENOMENA ANAK JALANAN DI KOTA KENDARI DALAM PERSPEKTIF HUKUM ISLAM - Ipandang Ipandang (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2016)
Abstract This study aims to explore the phenomenon of street children at Kendari city in Islamic law perspective. Using descriptive qualitative   and   theoretical approach of Islamic jurisprudence, it found that  there are  two  causes the children took to the streets  (1) the motivating factors include the insistence and the economic conditions, (2) the attracting factors  include   interesting  in a more independent life,  being  free to play,  having a lot of friends and money. Government efforts to provide guidance to them are (1) doing  integrated guidance system ranging from household environment, community, and municipal governments of  Kendari  with early treatment at the village level,  (2) building  a comprehensive understanding of the children's position in life through religious guidance, economic empowerment and improvement of skills,  (3) coordinated approach to all the elements, particularly NGO through various activities.                                                                                     Keywords: street children, Islamic law perspectiveAbstrakHasil penelitian ini mengkaji tentang penomena anak jalanan di Kota Kendari dalam Perspektif hukum Islam. Adapun sub masalahnya adalah sebagai berikut: pertama, apa yang menjadi faktor penyebab munculnya anak jalanan di Kota Kendari?, Kedua, bagaimana upaya pembinaan anak jalanan yang dilakukan pemerintah Kota Kendari?, Ketiga, bagaimana kedudukan anak jalanan dalam perspektif hukum islam di Kota Kendari?. Hasil penelitian menunjukkan bahwa penyebab munculnya anak jalanan di Kota Kendari disebabkan karna adanya akumulasi masalah mulai dari siuasi makro, kondisi orang tua, serta anak itu sendiri. Penyebab munculnya disebabkan oleh faktor pendorong dan faktor penarik. Faktor pendorong adalah desakan dan keadaan ekonomi. Faktor penarik adalah anak turun kejalan karna tertarik pada kehidupan yang lebih merdeka, bisa bebas bermain, banyak teman, dan banyak uang.